Digital Accessibility in Handicapped Persons - Kinali, Gulsah; Bilen, Omer; Doganay, Fatma; Abakay, Oguzhan (IEEE, 2017)
Studies about improving of health quality conditions of handicapped members is getting increase. Internet become one of the important part of human life in todays. Accessibility is a term that determine of using systems and product by everyone. Our aim in this study to determine difficulties of handicapped persons to use internet and smart phone. According to results of the study, handicapped persons have technic difficulty in internet using (%91,8), also they are thinking this situation keep them away from social life (%76,3). Handicapped persons have specific requirements in order to improve their internet using such as visual and voice guide (%46,4), much more clear signals (%46,0) and also accessible web pages (%45,1). According to our study we decided that, digital accessibility products production need to be accelerate with collaboration of production companies and universities.
Keywords: accessebility; Internet; assistive systems; ASSISTIVE TECHNOLOGY; Engineering